Développement professionnel d’un chercheur dans une recherche-action participative. Récit et analyse - Claire Matteï-Mieusset; Pierre Boudreau (Recherches en Éducation)
This article presents a narrative of the professional development of a faculty-instructor engaged in a participatory action research focused on the development of mentoring skills of cooperating teachers. The theoretical frameworks are highlighted and have been used to analyze the data collected over the three years of the project. The narrative and its analysis revealed a complex and dynamic professional development journey on a new re-search approach. This learning was made possible by the prolonged engagement in the project and a collaborative climate amongst the members (8) of the research group as well as their support and challenge. This article opens a different perspective on the professional development of the knowledge and skills of faculty.